PENGARUH PRODUK DAN LOKASI TERHADAP PENGAMBILAN KEPUTUSAN KONSUMEN PADA RUMAH MAKAN SAMO RASO PALEMBANG - Nirwan Rasyid (Orasi Bisnis : Jurnal Ilmiah Administrasi Niaga, 2013)
This study is to determine the effects of product and location on consumer purchasing decision at rumah makan Sama Raso Palembang. The purpose of research is to determine which variables are most dominant in influencing consumer consumer purchasing decisions. Data obtained from the questionnaires, obrservations, interviews, and the data were analyzed using multiple linear regression, correlation, and coefficient determination. The result show that there is a strong relation between two variables. Product influence positive and siginificant on consumer purchasing decision. Location influence positive and siginificant on consumer purchasing decision. Suggests to rumah makan samo raso to keep improve both the reference variables that product in quality and the location because that is logical reason comsumers in deciding to make a purchase.